2021
DOI: 10.3389/fped.2020.624915
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Imaging to Evaluate Food Passage Rate in Preterm Piglets as a Model for Preterm Infants

Abstract: Objectives and study: Gut motility in infants mature with increasing post-menstrual age and is affected by numerous hormonal, immunological and nutritional factors. However, it remains unclear how age and diet influence gut motility and its relation to feeding intolerance and gastric residuals in preterm neonates. Using preterm piglets as a model for infants, we investigated if contrast passage rate, as determined by X-ray contrast imaging, is affected by gestational age at birth, advancing postnatal age and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Statistically, the presence of GR (regardless of volume) had no negative effect on the following feeding volume, indicating that neither BC nor CF increased FI. Infants fortified with BC had a lower stomach appearance score, potentially reflecting a more mature gut, including improved motility and digestive function, as suggested by preterm piglets fortified with BC [47,48].…”
Section: Discussionmentioning
confidence: 93%
“…Statistically, the presence of GR (regardless of volume) had no negative effect on the following feeding volume, indicating that neither BC nor CF increased FI. Infants fortified with BC had a lower stomach appearance score, potentially reflecting a more mature gut, including improved motility and digestive function, as suggested by preterm piglets fortified with BC [47,48].…”
Section: Discussionmentioning
confidence: 93%
“…To choose the best food supply during the crucial newborn period, studies on physiological adaptation in preterm pigs are helpful (Sangild et al, 2013;Baek et al, 2019;Ahnfeldt et al, 2020). Therefore, preterm pigs are a good model to research the effects of preterm feeding tolerance, GIT maturation, microbial colonization, immunological activation, and growth (Obelitz-Ryom et al, 2018;Kappel et al, 2020). Using preterm pig models, the researchers found that pasteurization improved the digestion of formula milk powder and decreased bacterial adhesion in the mucosa of the proximal small intestine of piglets (Navis et al, 2020).…”
Section: Research Applications For Preterm Pig Modelsmentioning
confidence: 99%
“…However, neither casein supplementation to whey-based formula nor rapid advancement of a diet with casein (intact or hydrolyzed) increased the NEC sensitivity in preterm pigs [ 304 , 308 ]. In fact, a moderate BC-induced retention of digesta in the stomach may promote digestion and gut maturation, relative to whey-based formulas, as indicated from food transit studies in preterm pigs [ 309 ].…”
Section: Possible Health Risks Of Using Bovine Colostrum In Pediatricsmentioning
confidence: 99%